Evaluation of PepT1 (SLC15A1) substrate characteristics of therapeutic cyclic peptides - Bajraktari-Sylejmani, Gzona; Linde, Teresa von; Burhenne, Jürgen; Haefeli, Walter E.; Sauter, Max; Weiß, Johanna (Pharmaceutics, 2022)
The human peptide transporter hPepT1 (SLC15A1), physiologically transporting dipeptides and tripeptides generated during food digestion, also plays a role in the uptake of small bioactive peptides and peptide-like drugs. Moreover, it might be addressed in prodrug strategies of poorly absorbed drugs. We hypothesised that the cyclic drug peptides octreotide and pasireotide could be substrates of this transporter because their diameter can resemble the size of dipeptides or tripeptides due to their strong structural curvature and because they reach the systemic circulation in Beagle dogs. For investigating possible hPepT1 substrate characteristics, we generated and characterised a CHO-K1 cell line overexpressing SLC15A1 by transfection and selection via magnetic beads. Possible inhibition of the uptake of the prototypical substrate Gly-Sar by octreotide and pasireotide was screened, followed by quantifying the uptake of the cyclic peptides in cells overexpressing SLC15A1 compared with the parental cell line. Although inhibition of Gly-Sar uptake was observed, uptake of octreotide and pasireotide was not increased in SLC15A1 overexpressing cells, indicating a lack of transport by hPepT1. Our data clearly indicate that octreotide and pasireotide are nonsubstrate inhibitors of hPepT1 and that their oral bioavailability cannot be explained by absorption via hPepT1.